Mechanobiology of the nucleus during the G2-M transition - Joana T. Lima; Jorge G. Ferreira (Nucleus, 2024)
Cellular behavior is continuously influenced by mechanical forces. These forces span the cytoskeleton and reach the nucleus, where they trigger mechanotransduction pathways that regulate downstream biochemical events. Therefore, the nucleus has emerged as a regulator of cellular response to mechanical stimuli. Cell cycle progression is regulated by cyclin-CDK complexes. Recent studies demonstrated these biochemical pathways are influenced by mechanical signals, highlighting the interdependence of cellular mechanics and cell cycle regulation. In particular, the transition from G2 to mitosis (G2-M) shows significant changes in nuclear structure and organization, ranging from nuclear pore complex (NPC) and nuclear lamina disassembly to chromosome condensation. The remodeling of these mechanically active nuclear components indicates that mitotic entry is particularly sensitive to forces. Here, we address how mechanical forces crosstalk with the nucleus to determine the timing and efficiency of the G2-M transition. Finally, we discuss how the deregulation of nuclear mechanics has consequences for mitosis.